If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n + -6(1 + -1n) = 4(2n + 3) 4n + (1 * -6 + -1n * -6) = 4(2n + 3) 4n + (-6 + 6n) = 4(2n + 3) Reorder the terms: -6 + 4n + 6n = 4(2n + 3) Combine like terms: 4n + 6n = 10n -6 + 10n = 4(2n + 3) Reorder the terms: -6 + 10n = 4(3 + 2n) -6 + 10n = (3 * 4 + 2n * 4) -6 + 10n = (12 + 8n) Solving -6 + 10n = 12 + 8n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-8n' to each side of the equation. -6 + 10n + -8n = 12 + 8n + -8n Combine like terms: 10n + -8n = 2n -6 + 2n = 12 + 8n + -8n Combine like terms: 8n + -8n = 0 -6 + 2n = 12 + 0 -6 + 2n = 12 Add '6' to each side of the equation. -6 + 6 + 2n = 12 + 6 Combine like terms: -6 + 6 = 0 0 + 2n = 12 + 6 2n = 12 + 6 Combine like terms: 12 + 6 = 18 2n = 18 Divide each side by '2'. n = 9 Simplifying n = 9
| (x-5)/5-3/(2y-1) | | -3(5n+8)=3 | | 30+0.5m=10+1m | | 1+r-2r-1=-2+7r | | .40x+7=3 | | 2times+5=19 | | x^4+16x^2+1=0 | | 9+4=210 | | 11x+3x+17+x+11=28 | | 3times+0.3=3.3 | | 3x+2+6=3x+18 | | 15.5=2/3x-1/2 | | 8+6=p+8 | | Y=1/6(3(-2)-5 | | 15-2x=4x+x | | 9x+6-3x-8-2x-5+x=18 | | 8=n-7-5 | | p/3(q/6)= | | 40/140,000 | | -6x+5=18x-6 | | 4x+16=8x+32 | | 9x-3(6-5x)=x-2(6x+9) | | 5g=508mg | | 36overb-3=0 | | 48/132 | | -82-8(-8-b)+5b= | | 54a^2+39ab-8b^2=0 | | 3(x+2)-5x=2(3-x) | | 2r+8(2+8r)-182= | | 1/4g+2/3G= | | -4(2-3x)=7-3(x-3) | | x+5+3x+6+7x-3=-14 |